Policy Model of Zoning System in the Admission of New Students and Their Prospects in Indonesia - Muhartono, Djoko Siswanto (Journal Corner of Education, Linguistics, and Literature, 2024)
This research aims to construct a policy model for new student admissions, abbreviated as PPDB, with a zoning system and its prospects. The research approach uses a qualitative approach with data sources from State Junior High School 1 or abbreviated as SMPN 1 Gampengrejo and State Junior High School 3 or abbreviated as SMPN 3 Plosoklaten, Kediri County. There were ten key informants involved in this study. The analysis method is a comparative method for constructing a model of a public administration system. The findings of the study are: (1) every admission of new students in the education unit is regulated by the ministry of primary and secondary education; (2) there are technical instructions from the district/city government; (3) there is a decree of the head of the education unit regarding the executive committee; (4) provision of complete data on prospective students in zoning in accordance with the provisions of the central government; (5) coordination between school principals and between school committees to ensure that prospective students get schools; (6) the head of the education unit supports the executive committee; (7) suppressing obstacles that interfere with the smooth implementation of the zoning system; (8) developing an effective public information system, through feedback to provide input to the PPBD implementation system; (9) the transformation from PPDB to the New Student Admission System (SPMB) at the philosophical level is relatively unchanged; and (10) the change of the student admission system, the important thing is that all children of school age, all are obliged to get a school with the principle of "education for all." The conclusion is that the implementation of new student admissions (PPDB) has an impact on the equitable distribution of access to education that is more equitable and quality and is still continuously being refined and ensuring that all prospective students get school.